Efficiency in Construction Arbitration Management - Herrada, Tatiana (2020)
Arbitration is the mechanism most widely used worldwide in resolving construction disputes. Nonetheless, arbitration faces challenges related to its costs and length. This phenomenon has caused the study and the proposal of several recommendations in construction arbitration, which embodies the best practices in the mitigation of the inefficiencies under analysis. Given that two of the main causes of the inefficiencies in international construction arbitration proceedings are direct or indirectly related to the arbitrator’s role, it is argued that an arbitrator’s proactive leadership and a fearless attitude toward the so-called due process paranoia might have a significant impact in increasing efficiency, which finally will benefit both arbitration users and arbitrators. Several measures have been recommended and implemented at international level in this regard. Those measures could be replicated in domestic construction arbitrations, as long as they do not contravene the Arbitration Act or institutional arbitrations rules.